Sodium citrate-mediated size-controllable gold layer-coated ferroferric oxide nanoparticles and aqueous phase preparation method thereof
The water phase preparation method mediated by sodium citrate, sodium citrate to modify the tetraxidine nanometer particles, and add sodium citrate, chlorochloride and hydroxyline under nitrogen protection to solve the preparation of large -sized gold in the existing technology The problem of layer -covered triple iron nanoparticles has achieved controlling size, adjustment of magnetic core size, and low cost, which is suitable for large -scale biomedical applications.
Patent Information
- Application Number
- CN202411458050.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to prepare large-size gold layer-coated iron tetroxide nanoparticles with good magnetic properties, and the traditional method has a complex preparation process and high cost, which limits its large-scale biomedical application.
Using a sodium citrate-mediated aqueous phase preparation method, sodium citrate is used to modify ferric oxide nanoparticles, and sodium citrate, chloroauric acid and hydroxylamine hydrochloride are added under nitrogen protection to achieve gold layer coating of ferric oxide. The size of the nanoparticles is controllable, the size of the magnetic core is adjustable, there is no intermediate layer, and the preparation is low-cost.
It achieves controllable size of Fe3O4@Au nanoparticles and adjustable magnetic core size, reduces preparation costs, simplifies the process flow, and is suitable for large-scale biomedical applications.
Smart Images

Figure CN119330409A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine, and specifically relates to a sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticle and an aqueous phase preparation method thereof. Background Art
[0002] In today's biomedical field, the rapid development of nanotechnology has provided unprecedented opportunities for the design and application of a new generation of biomedical materials. In this field, magnetic gold nanoparticles have attracted much attention due to their unique physical and chemical properties and broad application prospects. The excellent optical properties, good biocompatibility, and easy biomodification of gold nanoparticles combined with the magnetic properties of magnetic materials make multifunctional magnetic gold nanoparticles show good application potential in biomedical fields such as bioimaging and in vitro detection.
[0003] There are many ways to prepare gold-coated magnetic nanoparticles (MNPs@Au). One way is chemical deposition (chemical reduction) method, which directly reduces gold ions on the surface of γ-Fe2O3 nanoparticles with hydroxylamine hydrochloride to prepare MNPs@Au with a core-shell structure. The chemical deposition (chemical reduction) method has the advantages of simple synthesis and mild synthesis conditions. The prepared MNPs@Au has good monodispersity and biocompatibility. Therefore, this method has become the preferred choice for preparing biomedical MNPs@Au. However, this method can only increase the particle size of nanoparticles by changing the thickness of the gold layer, so that the magnetic properties of nanoparticles decrease with the increase of nanoparticle size, and it is difficult to prepare large-sized MNPs@Au with good magnetic properties. Another way is to prepare MNPs@Au with an intermediate layer, by using oleylamine, polymer or silica as the intermediate layer to pre-coat magnetic nanoparticles, and then reducing gold ions on the surface of the intermediate layer to generate a gold layer, so that the problem of decreased magnetic properties of MNPs@Au after the particle size increases is improved. MNPs@Au with an intermediate layer has the characteristics of controllable size and adjustable component ratio. However, due to the introduction of the intermediate layer, its preparation process is relatively complicated and the preparation cost is high, which limits its large-scale biomedical application.
[0004] Therefore, it is necessary to develop Fe3O4@Au nanoparticles and their preparation methods that have good monodispersity, controllable size, and stable saturation magnetization and zeta potential at different particle sizes. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the present invention develops a sodium citrate-mediated size-controllable gold layer-coated ferroferric oxide nanoparticle (Fe3O4@Au) and an aqueous phase preparation method thereof, which realizes the size-controllable, magnetic core-adjustable, intermediate-layer-free and low-cost preparation of Fe3O4@Au nanoparticles.
[0006] To solve the above technical problems, the embodiments of the present invention adopt the following technical solutions:
[0007] The first object of the present invention is to provide a sodium citrate-mediated aqueous method for preparing size-controllable gold-coated ferroferric oxide nanoparticles, comprising the following steps:
[0008] Step 10, preparing a sodium citrate-modified ferroferric oxide nanoparticle solution;
[0009] Step 20, adding sodium citrate solution, chloroauric acid solution and hydroxylamine hydrochloride solution to the sodium citrate-modified ferroferric oxide nanoparticle solution to prepare gold-layer-coated ferroferric oxide nanoparticles.
[0010] As a further improvement of the embodiment of the present invention, the step 20 specifically includes:
[0011] Step 201, under nitrogen protection, adding a sodium citrate solution to a sodium citrate-modified ferroferric oxide nanoparticle solution to obtain a first reaction solution;
[0012] Step 202, adding chloroauric acid solution to the first reaction solution to obtain a second reaction solution;
[0013] Step 203, adding hydroxylamine hydrochloride solution to the second reaction solution to react to obtain a post-reaction solution containing gold-layer-coated ferrosoferric oxide nanoparticles;
[0014] Step 204 , collecting the gold-coated ferrosoferric oxide nanoparticles from the post-reaction solution.
[0015] As a further improvement of the embodiment of the present invention, in step 201, by adjusting the concentration of sodium citrate in the first reaction solution, gold-layer-coated ferrosoferric oxide nanoparticles having a target size can be obtained.
[0016] As a further improvement of the embodiment of the present invention, there is a negative correlation between the concentration of sodium citrate in the first reaction solution and the size of the ferrosoferric oxide nanoparticles coated with the gold layer.
[0017] As a further improvement of the embodiment of the present invention, in step 203, before adding the hydroxylamine hydrochloride solution to the second reaction solution, the pH of the second reaction solution is adjusted to a weak alkaline state using a sodium hydroxide solution.
[0018] As a further improvement of the embodiment of the present invention, in step 203, when the color of the reaction solution turns into wine red, chloroauric acid solution and hydroxylamine hydrochloride solution are added, and the UV-visible absorption spectrum of the generated gold layer-coated ferroferric oxide nanoparticles is detected until the UV-visible absorption peak intensity reaches saturation and before a significant red shift occurs, the addition of chloroauric acid solution and hydroxylamine hydrochloride solution is stopped.
[0019] As a further improvement of the embodiment of the present invention, the step 10 specifically includes:
[0020] Step 101, in a nitrogen atmosphere, mixing a ferroferric oxide nanoparticle solution and a sodium citrate solution, and incubating once, and when the zeta potential of the ferroferric oxide nanoparticle solution changes from a positive value to a negative value, obtaining a primary incubation solution, and storing it;
[0021] Step 102, magnetically separating the stored primary incubation solution to obtain incubated ferrosoferric oxide nanoparticles, then redissolving the incubated ferrosoferric oxide nanoparticles in deionized water, adding sodium citrate solution, and performing a secondary incubation to obtain a secondary incubation solution after 24 hours;
[0022] Step 103, washing the secondary incubation solution and redissolving it in deionized water to obtain a sodium citrate-modified ferrosoferric oxide nanoparticle solution.
[0023] As a further improvement of the embodiment of the present invention, the concentration of the sodium citrate solution in step 102 is higher than the concentration of the sodium citrate solution in step 101.
[0024] As a further improvement of the embodiment of the present invention, before step 101, the method further includes: step 100, preparing a solution of ferrosoferric oxide nanoparticles.
[0025] As a further improvement of the embodiment of the present invention, in step 100, the ferrosoferric oxide nanoparticle solution is prepared by a coprecipitation method; specifically, the method includes:
[0026] Ferric chloride hexahydrate and ferrous chloride tetrahydrate are dissolved in water, placed in a water bath, heated and stirred, and nitrogen is introduced, and concentrated ammonia water is added dropwise and at a uniform rate and stirred and incubated; after the reaction is completed, the generated ferrosoferric oxide nanoparticles are collected by a magnetic separation method, washed, and then the ferrosoferric oxide nanoparticles are dispersed in deionized water to obtain a ferrosoferric oxide nanoparticle solution.
[0027] The second object of the present invention is to provide sodium citrate-mediated, size-controllable gold-layer-coated ferroferric oxide nanoparticles, wherein the sodium citrate-mediated, size-controllable gold-layer-coated ferroferric oxide nanoparticles are prepared by the aforementioned preparation method.
[0028] Compared with the prior art, the aqueous phase preparation method of size-controllable Fe3O4@Au nanoparticles mediated by sodium citrate provided by the present invention comprises the following steps: firstly preparing a sodium citrate-modified ferroferric oxide (Fe3O4) nanoparticle solution, and then adding a sodium citrate solution, a chloroauric acid solution and a hydroxylamine hydrochloride solution to the sodium citrate-modified Fe3O4 nanoparticle solution to prepare Fe3O4@Au nanoparticles; the present invention firstly uses sodium citrate to modify the surface of the Fe3O4 nanoparticles so that the surface potential of the Fe3O4 nanoparticles changes from positive to negative, and then adds a sodium citrate solution, a chloroauric acid solution and a hydroxylamine hydrochloride solution, the Fe3O4 nanoparticles are used as magnetic cores, and the hydroxylamine hydrochloride is used as a reducing agent to reduce the chloroauric acid so that gold is wrapped on the surface of the Fe3O4 nanoparticles, and the sodium citrate is used as a ligand to synchronously adjust the internal magnetic core size and the external gold layer size composed of the Fe3O4 nanoparticles, thereby achieving the purpose of adjusting the size of the Fe3O4@Au nanoparticles, rather than achieving the purpose of adjusting the size of the Fe3O4@Au nanoparticles by adjusting the external gold layer size. The invention realizes the controllable size of Fe3O4@Au nanoparticles, the adjustable size of magnetic core, the absence of intermediate layers and low-cost preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a flow chart of the aqueous phase preparation method of Fe3O4@Au nanoparticles with controllable size mediated by sodium citrate provided by the present invention;
[0030] Figure 2 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 1. Figure 2 (b) is a scanning transmission electron microscopy photograph of the Fe3O4@Au nanoparticles prepared in Example 1;
[0031] Figure 3 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 2. Figure 3 (b) is a scanning transmission electron microscopy photograph of Fe3O4@Au nanoparticles prepared in Example 2;
[0032] Figure 4 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 3. Figure 4 (b) is a scanning transmission electron micrograph of the Fe3O4@Au nanoparticles prepared in Example 3;
[0033] Figure 5 (a) is an X-ray powder diffraction pattern of Fe3O4 nanoparticles obtained in the preparation process of Example 1, Example 2 and Example 3, and Fe3O4@Au nanoparticles of different sizes finally prepared; Figure 5(b) is a graph showing the magnetization curves of the Fe3O4 nanoparticles obtained in the preparation process of Example 1, Example 2 and Example 3, and the Fe3O4@Au nanoparticles of different sizes finally prepared; Figure 5 (c) is the average Zeta potential of the Fe3O4 nanoparticles obtained in the preparation process of Example 1, Example 2 and Example 3, the Fe3O4 nanoparticles modified with sodium citrate, and the Fe3O4@Au nanoparticles of different sizes finally prepared;
[0034] Figure 6 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 1. Figure 6 (b) is a scanning transmission electron microscopy photograph of Fe3O4@Au nanoparticles prepared in Comparative Example 1;
[0035] Figure 7 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 2. Figure 7 (b) is a scanning transmission electron microscopy photograph of Fe3O4@Au nanoparticles prepared in Comparative Example 2;
[0036] Figure 8 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 3. Figure 8 (b) is a scanning transmission electron microscopy photograph of Fe3O4@Au nanoparticles prepared in Comparative Example 3;
[0037] Fig. 9 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 4. Fig. 9 (b) is a scanning transmission electron microscopy photograph of Fe3O4@Au nanoparticles prepared in Comparative Example 4;
[0038] Fig.10 (a) is the UV-visible absorption spectrum of Fe3O4@Au nanoparticles prepared in Example 5. Fig.10 (b) is a scanning transmission electron microscopy photograph of the Fe3O4@Au nanoparticles prepared in Comparative Example 5. DETAILED DESCRIPTION
[0039] The present invention is further explained below with reference to the examples, but the examples do not limit the present invention in any form.
[0040] The present invention provides a sodium citrate-mediated aqueous method for preparing size-controllable Fe3O4@Au nanoparticles. Figure 1 As shown, the following steps are included:
[0041] Step 10, preparing a sodium citrate-modified Fe3O4 nanoparticle solution.
[0042] Step 20, adding sodium citrate solution, chloroauric acid solution and hydroxylamine hydrochloride solution to the sodium citrate-modified Fe3O4 nanoparticle solution to prepare Fe3O4@Au nanoparticles.
[0043] In the embodiment of the present invention, sodium citrate is first used as a ligand to modify the surface of Fe3O4 nanoparticles, so that the surface potential of Fe3O4 nanoparticles changes from positive to negative, so that gold can be smoothly wrapped on the surface of Fe3O4 nanoparticles in the future. Then sodium citrate solution, chloroauric acid solution and hydroxylamine hydrochloride solution are added, Fe3O4 nanoparticles are used as magnetic cores, hydroxylamine hydrochloride is used as a reducing agent to reduce chloroauric acid, so that chloroauric acid wraps part of Fe3O4 nanoparticles as magnetic cores while reducing to gold, and sodium citrate is used as a size regulator to synchronously adjust the internal magnetic core size and the external gold layer size of the Fe3O4 nanoparticle composition, thereby achieving the purpose of adjusting the size of Fe3O4@Au nanoparticles, not only adjusting the external gold layer size to achieve the purpose of adjusting the size of Fe3O4@Au nanoparticles. Therefore, this embodiment realizes the controllable size of Fe3O4@Au nanoparticles, the adjustable size of the magnetic core, no intermediate layer, and low-cost preparation.
[0044] In the embodiment of the present invention, sodium citrate, as a surface ligand, will be adsorbed on the surface of the newly generated gold layer and hinder the surface of the nanoparticles from continuing to reduce and grow, thereby achieving the effect of limiting the size of the nanoparticles finally generated. The amount of sodium citrate adsorbed on the surface of the gold layer of different concentrations is different, so that the size of the limiting effect is different, thereby obtaining Fe3O4@Au nanoparticles of different sizes. Under the condition of fixed chloroauric acid concentration, hydroxylamine hydrochloride reducing agent concentration, and magnetic core concentration, different concentrations of sodium citrate are used for adjustment to obtain nanoparticles of different sizes. Only the amount of sodium citrate is changed, and sodium citrate does not participate in the reduction reaction (room temperature and in a weakly alkaline environment), and Fe3O4@Au nanoparticles of different sizes with different magnetic core volumes can be obtained, and the magnetic core volume is proportional to the size of the nanoparticles. After obtaining the Fe3O4@Au nanoparticles, the seed growth method is used to continue to epitaxially grow the gold layer on the surface of the Fe3O4@Au nanoparticles, thereby obtaining Fe3O4@Au nanoparticles with different gold layer thicknesses.
[0045] As a preferred example, the above step 10 specifically includes:
[0046] Step 100, preparing a Fe3O4 nanoparticle solution.
[0047] One solution is to directly disperse the purchased Fe3O4 nanoparticles in deionized water to obtain a Fe3O4 nanoparticle solution.
[0048] Preferably, this embodiment provides another solution, using a co-precipitation method to prepare a Fe3O4 nanoparticle solution.
[0049] Specifically, ferric chloride hexahydrate and ferrous chloride tetrahydrate are dissolved in water, placed in a water bath for heating and stirring, and nitrogen is introduced, and concentrated ammonia water is added dropwise at a uniform rate and stirred for incubation. After the reaction is completed, the generated Fe3O4 nanoparticles are collected by a magnetic separation method, washed, and then dispersed in deionized water to obtain a Fe3O4 nanoparticle solution.
[0050] Step 101, in a nitrogen atmosphere, Fe3O4 nanoparticle solution and sodium citrate solution are mixed and incubated once, and when the Zeta potential of the ferroferric oxide nanoparticle solution changes from a positive value to a negative value, an incubation solution is obtained and stored.
[0051] After one incubation, sodium citrate is adsorbed on the surface of Fe3O4 nanoparticles as a ligand, so that the Fe3O4 nanoparticles are initially modified by sodium citrate, and their surface potential changes from positive to negative, thereby increasing their storage stability.
[0052] Step 102, under a nitrogen atmosphere, magnetically separate the first incubation solution to obtain incubated Fe3O4 nanoparticles, then redissolve the incubated Fe3O4 nanoparticles in deionized water, add sodium citrate solution, and incubate for a second time. After 24 hours, a secondary incubation solution is obtained.
[0053] The secondary incubation time is longer than the primary incubation time. During the secondary incubation, sodium citrate is adsorbed on the surface of Fe3O4 nanoparticles as a ligand, so that the surface of Fe3O4 nanoparticles is completely modified by sodium citrate, so that it can be smoothly coated with a gold layer in subsequent steps.
[0054] Both the first incubation and the second incubation were carried out under nitrogen protection to prevent the Fe3O4 nanoparticles from being oxidized to Fe2O3 nanoparticles.
[0055] Preferably, the concentration of the sodium citrate solution in step 102 is higher than that in step 101. Moreover, the secondary incubation time is longer than the primary incubation time.
[0056] Step 101 and step 102 are repeated steps to modify Fe3O4 nanoparticles with sodium citrate. Since the binding between sodium citrate and Fe3O4 nanoparticles is based on electrostatic adsorption rather than covalent binding, the binding effect is weak and is affected by the pH of the solution and the concentration of sodium citrate ligands. In order to prepare Fe3O4 nanoparticles stabilized with sodium citrate, we first co-incubate Fe3O4 nanoparticles with low concentrations of sodium citrate in step 101, and then in step 102, Fe3O4 nanoparticles modified with sodium citrate are incubated with a higher concentration of sodium citrate for a second time, and the second incubation time is longer than the first time, so as to stabilize the modification of sodium citrate and allow the adsorption of sodium citrate ligands by Fe3O4 nanoparticles to reach saturation.
[0057] Step 103, washing the secondary incubation solution and redissolving it in deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0058] The secondary incubation solution is washed to remove excess sodium citrate in the secondary incubation solution to prevent deviation in the concentration of sodium citrate in the subsequent reaction solution, thereby affecting the adjustment of the size of the Fe3O4@Au nanoparticles.
[0059] As a preferred example, the above step 20 specifically includes:
[0060] Step 201, under nitrogen protection, adding sodium citrate solution to the sodium citrate-modified Fe3O4 nanoparticle solution to obtain a first reaction solution.
[0061] Preferably, based on the negative correlation between the concentration of sodium citrate in the first reaction solution and the size of the Fe3O4@Au nanoparticles, Fe3O4@Au nanoparticles with a target size can be obtained by adjusting the concentration of sodium citrate in the first reaction solution.
[0062] In the reaction of generating Fe3O4@Au nanoparticles, sodium citrate mainly acts as a size regulator and does not participate in the reduction of chloroauric acid. When small-sized Fe3O4@Au nanoparticles need to be prepared, the concentration of sodium citrate in the first reaction solution is relatively high; when medium-sized Fe3O4@Au nanoparticles need to be prepared, the concentration of sodium citrate in the first reaction solution is lower than the concentration of sodium citrate in the first reaction solution when small-sized Fe3O4@Au nanoparticles are prepared; when large-sized Fe3O4@Au nanoparticles need to be prepared, the concentration of sodium citrate in the first reaction solution is lower than the concentration of sodium citrate in the first reaction solution when medium-sized Fe3O4@Au nanoparticles are prepared. For example, to the same amount of sodium citrate-modified Fe3O4 nanoparticle solution, 500-1000 μL of 25 mM sodium citrate is added to obtain the first reaction solution, and the size of the generated Fe3O4@Au nanoparticles is regulated to be 25±5 nm; 250-400 μL of 25 mM sodium citrate is added to regulate the size of the generated Fe3O4@Au nanoparticles to be 45±5 nm; 50-150 μL of 25 mM sodium citrate is added to regulate the size of the generated Fe3O4@Au nanoparticles to be 85±10 nm. If the concentration of sodium citrate is too high, it will directly participate in the reaction to reduce chloroauric acid, resulting in the formation of gold nanoparticles; if the concentration of sodium citrate is too low, the size of the generated Fe3O4@Au nanoparticles will increase, the monodispersity will decrease, and Fe3O4@Au nanoparticles with good monodispersity cannot be generated.
[0063] In a neutral and ligand-free environment, a portion of the sodium citrate ligands on the surface of the Fe3O4 nanoparticles modified with sodium citrate will fall off from the surface of the nanoparticles and become free in the solution due to the dissociation-adsorption equilibrium. To avoid this, sodium citrate is added to place the nanoparticles in an environment with a slight excess of ligands, thereby slowing down the shedding of the sodium citrate ligands from the surface of the Fe3O4 nanoparticles. In addition, the incubation environment of the high concentration of ligands in step 102 has ensured the saturated adsorption of sodium citrate, and the sodium citrate added in step 201 provides a slight excess environment of sodium citrate and a size control effect on the Fe3O4@Au nanoparticles.
[0064] Step 202, after the sodium citrate in the first reaction solution is fully adsorbed on the surface of the Fe3O4 nanoparticles, a chloroauric acid solution is added to obtain a second reaction solution.
[0065] For example, after the first reaction solution is stirred for 20 minutes, it can be considered that sufficient adsorption has been completed.
[0066] Step 203, adjusting the pH of the second reaction solution to weak alkalinity using a sodium hydroxide solution, and adding a hydroxylamine hydrochloride solution to the second reaction solution.
[0067] In the reaction of generating Fe3O4@Au nanoparticles, hydroxylamine hydrochloride is used as a reducing agent to reduce chloroauric acid. The pH of the second reaction solution is adjusted to a weak alkaline state, so that the reducing property of hydroxylamine hydrochloride is the strongest and the synthesis effect is the best. If the reducing property of hydroxylamine hydrochloride is weak under neutral conditions, the synthesis reaction effect is poor; if the reducing property of hydroxylamine hydrochloride is extremely weak under acidic conditions, it cannot reduce chloroauric acid, resulting in the failure of the synthesis reaction.
[0068] After a period of reaction, chloroauric acid solution and hydroxylamine hydrochloride solution are added, and the UV-visible absorption spectrum of the generated Fe3O4@Au nanoparticles is detected until the UV-visible absorption peak intensity reaches saturation and before a significant red shift occurs, the addition of chloroauric acid solution and hydroxylamine hydrochloride solution is stopped to obtain a post-reaction solution containing Fe3O4@Au nanoparticles.
[0069] Add chloroauric acid solution and hydroxylamine hydrochloride solution to completely convert Fe3O4 nanoparticles that are not coated by the gold layer in the solution into Fe3O4@Au nanoparticles. When there are uncoated Fe3O4 nanoparticles in the solution, the newly reduced gold will preferentially coat the Fe3O4 nanoparticles to generate Fe3O4@Au nanoparticles, resulting in an increase in the intensity of the UV-visible absorption peak. Before the intensity of the UV-visible absorption peak reaches saturation and a significant red shift occurs, stop adding chloroauric acid solution and hydroxylamine hydrochloride solution to prevent excess gold from being reduced on the surface of the Fe3O4@Au nanoparticles, resulting in an increase in the thickness of the gold layer and an increase in the overall size of the nanoparticles.
[0070] Step 204, collecting Fe3O4@Au nanoparticles from the post-reaction solution.
[0071] Three examples and six comparative examples are provided below to verify the performance of the method of the embodiment of the present invention.
[0072] Example 1 Preparation of small-sized Fe3O4@Au nanoparticles (25 nm)
[0073] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0074] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0075] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 500μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 227.27μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns to wine red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0076] like Figure 2 As shown, the ultraviolet-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Example 1 is 527-529 nm, the particle size distribution is 24.4-32.1 nm, and the Zeta potential is -29.56 mV.
[0077] Example 2 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0078] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0079] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0080] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 350μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 159.09μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns to wine red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0081] like Figure 3 As shown, the UV-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Example 2 is 536-542 nm, the particle size distribution is 44.0-46.7 nm, and the Zeta potential is -28.19 mV.
[0082] Example 3 Preparation of large-sized Fe3O4@Au nanoparticles (85 nm)
[0083] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0084] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0085] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 50μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 22.73μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns to wine red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0086] like Figure 4 As shown, the UV-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Example 3 is 555-560 nm, the particle size distribution is 79.6-83.3 nm, and the Zeta potential is -30.93 mV.
[0087] Experimental Example 1
[0088] The Fe3O4@Au nanoparticles prepared in Example 1, Example 2 and Example 3 were subjected to X-ray powder diffraction. Figure 5As can be seen in (a), Fe3O4@Au nanoparticles of different sizes all have characteristic absorption peaks of gold and Fe3O4. The Fe3O4@Au nanoparticles prepared in Example 1, Example 2 and Example 3 were tested using a vibrating sample magnetometer. Figure 5 As can be seen in (b), Fe3O4@Au nanoparticles of different sizes have similar saturation magnetization. Figure 5 As can be seen from (c), the average Zeta potential of the Fe3O4 nanoparticles prepared by the co-precipitation method is +21.65 mV; the average zeta potential of the Fe3O4 nanoparticles modified with sodium citrate is -36.25 mV; the Zeta potentials of the Fe3O4@Au nanoparticles of different sizes prepared are relatively close, with an average value of -29.56 mV.
[0089] ICP-Mass was used to measure the element contents of the Fe3O4@Au nanoparticle solutions prepared in Example 1, Example 2 and Example 3. The Fe3O4@Au nanoparticles with a target diameter of 25 nm prepared in Example 1 contained 86.87891 mg / L of gold and 47.14271 mg / L of iron; the Fe3O4@Au nanoparticles with a target diameter of 45 nm prepared in Example 2 contained 87.02816 mg / L of gold and 47.08316 mg / L of iron; the Fe3O4@Au nanoparticles with a target diameter of 85 nm prepared in Example 3 contained 87.04332 mg / L of gold and 46.94583 mg / L of iron. This indicates that the Fe3O4@Au nanoparticles were successfully synthesized.
[0090] The density of Fe3O4 is 5.17 g / cm 3 And the density of gold is 19.32g / cm 3 If the Fe3O4@Au nanoparticles are equivalent to a nanostructure with a solid Fe3O4 magnetic core inside and a gold layer coating outside, then for the Fe3O4@Au nanoparticles with a target diameter of 25nm prepared in Example 1, the equivalent radius of the Fe3O4 magnetic core inside is 9.18nm, and the thickness of the gold layer is 3.32nm; for the Fe3O4@Au nanoparticles with a target diameter of 45nm prepared in Example 2, the equivalent radius of the Fe3O4 magnetic core inside is 16.51nm, and the thickness of the gold layer is 5.99nm; for the Fe3O4@Au nanoparticles with a target diameter of 85nm prepared in Example 3, the equivalent radius of the Fe3O4 magnetic core inside is 31.18nm, and the thickness of the gold layer is 11.32nm. This shows that the size of the internal magnetic core and the size of the external gold layer of the Fe3O4 nanoparticles are synchronously adjusted.
[0091] Comparative Example 1 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0092] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0093] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0094] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 350μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 159.09μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to neutral with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns purple-red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0095] like Figure 6 As shown, the ultraviolet-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Comparative Example 1 is 545-555 nm, the particle size distribution is 40.3-70.1 nm, and the Zeta potential is -22.28 mV.
[0096] Comparative Example 2 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0097] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0098] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0099] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 350μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 159.09μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak acidity with hydrochloric acid solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution did not change significantly, and then chloroauric acid solution and hydroxylamine hydrochloride solution were added in turn, but no obvious absorption peak appeared in the UV-visible absorption spectrum. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0100] like Figure 7 As shown, the Fe3O4@Au nanoparticles prepared in Comparative Example 2 have no obvious UV-visible absorption peak, a particle size distribution of 6.3 to 13.4 nm, and a Zeta potential of -16.25 mV.
[0101] Comparative Example 3 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0102] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0103] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0104] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns reddish brown, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation. Collect Fe3O4@Au nanoparticles from the solution after the reaction.
[0105] like Figure 8 As shown, the ultraviolet-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Comparative Example 3 is 654-670 nm, the particle size distribution is 498.7-512.3 nm, and the Zeta potential is 11.13 mV.
[0106] Comparative Example 4 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0107] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0108] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0109] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 1000μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 454.54μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns orange-red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0110] like Fig. 9 As shown, the ultraviolet-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Comparative Example 4 is 522-523 nm, the particle size distribution is 20.2-22.5 nm, and the Zeta potential is -29.76 mV.
[0111] Comparative Example 5 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0112] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0113] Under nitrogen protection, 4 mL of the Fe3O4 nanoparticle solution co-incubated with the sodium citrate solution was magnetically separated and re-dissolved with 20 mL of deionized water, and then ligand adsorbed with 20 mL of 0.1 M sodium citrate solution and stirred for 24 h to obtain a secondary incubation solution. The solution after ligand adsorption was washed and re-dissolved in 40 mL of deionized water to obtain a sodium citrate-modified Fe3O4 nanoparticle solution.
[0114] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 2000μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 909.08μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns dark red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0115] like Fig.10 As shown, the ultraviolet-visible absorption peak of the Fe3O4@Au nanoparticles prepared in Comparative Example 5 is 520-522 nm, the particle size distribution is 14.3-30.8 nm, and the Zeta potential is -37.31 mV.
[0116] Comparative Example 6 Preparation of medium-sized Fe3O4@Au nanoparticles (45 nm)
[0117] 400mg FeCl3·6H2O (1.48mmol) and 200mg FeCl2·4H2O (1.01mmol) were dissolved in 50mL water, heated in a 60℃ water bath and stirred vigorously, and nitrogen was introduced to protect the reaction. 5mL 28% concentrated ammonia water was added dropwise at a rate of 600mL / h using a syringe pump and stirred and incubated for 20 minutes. The reaction solution gradually changed from clear yellow to shiny black. After the reaction was completed, the generated Fe3O4 nanoparticles were collected by magnetic separation, washed twice with 50mL water, and then dispersed in 50mL deionized water. The obtained Fe3O4 nanoparticles were stirred and incubated with 10mL 0.01M sodium citrate solution under a nitrogen atmosphere for 2h. When the Zeta potential of the ferroferric oxide nanoparticle solution changed from positive to negative, an incubation solution was obtained, and the obtained black solution was stored at 4℃ for later use.
[0118] Take 2mL of sodium citrate-modified Fe3O4 nanoparticle solution and dilute it to 55mL with deionized water. Then, under vigorous stirring and nitrogen protection, add 350μL of 25mM sodium citrate solution to make the sodium citrate concentration in the reaction solution 159.09μM. After stirring for 20min, add 500μL of 25mM chloroauric acid solution, and adjust the pH of the reaction solution to weak alkalinity with sodium hydroxide solution, and then add 500μL of 0.4M hydroxylamine hydrochloride solution. After 10 minutes of reaction, the color of the reaction solution turns purple-red, and chloroauric acid solution and hydroxylamine hydrochloride solution are added in sequence until the UV-visible absorption peak intensity reaches saturation and stops before a significant red shift occurs. Collect Fe3O4@Au nanoparticles from the post-reaction solution.
[0119] The Fe3O4@Au nanoparticles prepared in Comparative Example 6 had a UV-visible absorption peak of 535-591 nm, a particle size distribution of 45-150 nm, and a Zeta potential of -28.19 mV.
[0120] Experimental Example 2
[0121] By comparing Example 2 with Comparative Example 1, it can be found that under neutral conditions, the ultraviolet-visible absorption peak distribution of the Fe3O4@Au nanoparticle solution prepared in Comparative Example 1 is relatively wide, and the monodispersity of the nanoparticles is relatively poor.
[0122] Comparing Example 2 with Comparative Example 2, it can be found that in Comparative Example 2, under weakly acidic conditions, the reaction solution obtained after the reaction is completed has no obvious UV-visible absorption peak, indicating that no obvious Fe3O4@Au nanoparticles are generated. In Example 2, under weakly alkaline conditions, Fe3O4@Au nanoparticles can be successfully synthesized, and the nanoparticles have high monodispersity.
[0123] By comparing Example 2 with Comparative Example 3, it can be found that the concentration of sodium citrate in the reaction system of Comparative Example 3 is too low, the prepared Fe3O4@Au nanoparticle solution has a wide UV-visible absorption peak distribution, the size of the nanoparticles is large, and it presents a nanoflower-like structure.
[0124] By comparing Example 2 with Comparative Example 4, it can be found that when the concentration of sodium citrate in the reaction system of Comparative Example 4 is high, the UV-visible absorption peak of the prepared Fe3O4@Au nanoparticle solution undergoes an obvious blue shift, and the particle size of the generated nanoparticles is smaller.
[0125] By comparing Example 2 with Comparative Example 5, it can be found that when the sodium citrate concentration in the reaction system of Comparative Example 5 is too high, the UV-visible absorption peak of the prepared Fe3O4@Au nanoparticle solution undergoes an obvious blue shift, the distribution becomes wider, and the generated nanoparticles have a smaller particle size and poor monodispersity. The sodium citrate concentration in the first reaction solution of Example 2 is appropriate, and Fe3O4@Au nanoparticles of the target particle size can be prepared.
[0126] Comparing Example 2 with Comparative Example 6, it can be found that in the reaction system of Comparative Example 6, since the Fe3O4 nanoparticles were not incubated twice with a high concentration of sodium citrate solution, sodium citrate did not reach saturated adsorption on the surface of the Fe3O4 nanoparticles, making it difficult to control the concentration of free sodium citrate in the first reaction solution, resulting in a wide distribution of the UV-visible absorption peak of the prepared Fe3O4@Au nanoparticle solution, a wide size distribution range of the nanoparticles, and poor monodispersity. In the first reaction solution of Example 2, the concentration of free sodium citrate can be more accurately controlled, and Fe3O4@Au nanoparticles with a high monodispersity and a target particle size can be prepared.
[0127] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing size-controllable gold-coated ferroferric oxide nanoparticles in an aqueous phase mediated by sodium citrate, characterized in that: The following steps are involved: Step 10, preparing a sodium citrate-modified ferroferric oxide nanoparticle solution; Step 20, adding sodium citrate solution, chloroauric acid solution and hydroxylamine hydrochloride solution to the sodium citrate-modified ferroferric oxide nanoparticle solution to prepare gold-layer-coated ferroferric oxide nanoparticles.
2. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 1, characterized in that: The step 20 specifically includes: Step 201, under nitrogen protection, adding a sodium citrate solution to a sodium citrate-modified ferroferric oxide nanoparticle solution to obtain a first reaction solution; Step 202, adding chloroauric acid solution to the first reaction solution to obtain a second reaction solution; Step 203, adding hydroxylamine hydrochloride solution to the second reaction solution for reaction to obtain a post-reaction solution containing ferrosoferric oxide nanoparticles coated with a gold layer; Step 204 , collecting the gold-coated ferrosoferric oxide nanoparticles from the post-reaction solution.
3. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 2, characterized in that: In step 201, by adjusting the concentration of sodium citrate in the first reaction solution, gold-coated ferroferric oxide nanoparticles of target size can be obtained, and there is a negative correlation between the concentration of sodium citrate in the first reaction solution and the size of the gold-coated ferroferric oxide nanoparticles.
4. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 2, characterized in that: In step 203, before adding the hydroxylamine hydrochloride solution to the second reaction solution, the pH of the second reaction solution is adjusted to a weak alkaline state using a sodium hydroxide solution.
5. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 2, characterized in that: In step 203, when the color of the reaction solution turns into wine red, chloroauric acid solution and hydroxylamine hydrochloride solution are added, and the UV-visible absorption spectrum of the generated gold layer-coated ferroferric oxide nanoparticles is detected until the UV-visible absorption peak intensity reaches saturation and before a significant red shift occurs, the addition of chloroauric acid solution and hydroxylamine hydrochloride solution is stopped.
6. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 1, characterized in that: The step 10 specifically includes: Step 101, in a nitrogen atmosphere, mixing a ferroferric oxide nanoparticle solution and a sodium citrate solution, and incubating once, and when the zeta potential of the ferroferric oxide nanoparticle solution changes from a positive value to a negative value, obtaining a primary incubation solution, and storing it; Step 102, magnetically separating the stored primary incubation solution to obtain incubated ferrosoferric oxide nanoparticles, then redissolving the incubated ferrosoferric oxide nanoparticles in deionized water, adding sodium citrate solution, and performing a secondary incubation to obtain a secondary incubation solution after 24 hours; Step 103, washing the secondary incubation solution and redissolving it in deionized water to obtain a sodium citrate-modified ferrosoferric oxide nanoparticle solution.
7. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 6, characterized in that: The concentration of the sodium citrate solution in step 102 is higher than the concentration of the sodium citrate solution in step 101.
8. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 6, characterized in that: Before step 101, the method further includes: step 100, preparing a solution of ferrosoferric oxide nanoparticles.
9. The aqueous phase preparation method of sodium citrate-mediated size-controllable gold layer-coated ferrosoferric oxide nanoparticles according to claim 8, characterized in that: In the step 100, a ferrosoferric oxide nanoparticle solution is prepared by a coprecipitation method; Specifically include: Ferric chloride hexahydrate and ferrous chloride tetrahydrate are dissolved in water, placed in a water bath, heated and stirred, and nitrogen is introduced, and concentrated ammonia water is added dropwise and at a uniform rate and stirred and incubated; after the reaction is completed, the generated ferrosoferric oxide nanoparticles are collected by a magnetic separation method, washed, and then the ferrosoferric oxide nanoparticles are dispersed in deionized water to obtain a ferrosoferric oxide nanoparticle solution.
10. A sodium citrate-mediated, size-controllable gold layer-coated ferroferric oxide nanoparticle, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of gold magnetic nano-enzyme and method for enhancing catalytic activity of gold magnetic nano-enzyme
CN120619380A